Penyuluhan Kesehatan Gizi sebagai Upaya Pencegahan Osteoporosis pada Lansia di Kalangan Ibu-Ibu Aisyiyah Kabupaten Cirebon - Marwati Marwati; Sofiyati Sofiyati (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing proportion of the elderly population in Indonesia has led to a rise in degenerative health problems, one of which is osteoporosis. Osteoporosis is a bone disease characterized by decreased bone density, increasing the risk of fractures, particularly among elderly women. Low calcium intake, lack of physical activity, and limited knowledge regarding osteoporosis prevention are major contributing factors. This community service activity aimed to improve the knowledge of Aisyiyah women in Cirebon Regency regarding osteoporosis in the elderly, including its definition, risk factors, impacts, and prevention strategies through proper nutrition and regular physical activity. The activity was conducted from October to December at the Aisyiyah Study Hall in Cirebon Regency, targeting pre-elderly and elderly women. The methods used included health education through lectures and interactive question-and-answer sessions, supported by laptops, LCD projectors, and PowerPoint presentations. Evaluation of participants’ knowledge was carried out using oral pre-tests and post-tests related to the delivered material. The results indicated an improvement in participants’ understanding of osteoporosis, the importance of adequate calcium intake, and the role of physical activity in maintaining bone health. This community service program is expected to contribute to increasing health awareness and reducing the risk and prevalence of osteoporosis among the elderly.